2020
DOI: 10.1039/c9qm00618d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quantum dots enhanced the activity for the hydrogen evolution reaction in ruthenium-based electrocatalysts

Abstract: The Ru supported on Porphyra-CQDs exhibited better dispersibility and the highest activity compared with biomass Porphyra and Porphyra activated carbon owing to the strong coordination interactions between Ru and CQDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…The number of electroactive sites and electrolyte ion accessibility play a major role in the performance of the electrochemical system along with the porosity, specific surface area, and morphology of the active material. 40 The combined effect of two different TMOs increases the number of electroactive sites as well as the potential window. In addition to their low-cost, abundant availability and eco-friendliness make MTMOs excellent candidates for active electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…The number of electroactive sites and electrolyte ion accessibility play a major role in the performance of the electrochemical system along with the porosity, specific surface area, and morphology of the active material. 40 The combined effect of two different TMOs increases the number of electroactive sites as well as the potential window. In addition to their low-cost, abundant availability and eco-friendliness make MTMOs excellent candidates for active electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…These properties also help CD particles to act as efficient support material towards metal and carbon (graphene, graphitic carbon nitrides etc.) by boosting their surface area to volume ratio and electronic properties [26][27][28][29][30][31]. Since their first application as electrocatalysts, there has been rapid development in CD based electrocatalysis, specifically, metal free carbon-based catalysts.…”
Section: -D CD Nanoparticles For Electrocatalysismentioning
confidence: 99%
“…Li et al, reported CQD supported enhanced activity of ruthenium (Ru) nanocatalyst for HER [31]. The catalytic activity largely depended on the crystallinity and confinement effects.…”
Section: Cnd/cqd Supported Metallic and Nonmetallic Nanoparticlesmentioning
confidence: 99%
“…[1,2] Hydrogen (H 2 ) is regarded as one of the most potential clean energy sources due to its high energy density, no carbon emission, and unpolluted feature. [3][4][5][6][7][8][9] Until now, electrochemical water splitting is deemed as an essential and effective method to prepare H 2 because of its high purity of product and little energy waste. [10][11][12][13] However, hydrogen evolution reaction (HER) in nonacidic conditions should be paid much attention because it is a direct hydrogen production half-reaction which reaction rate is much more sluggish than that in acid.…”
Section: Introductionmentioning
confidence: 99%